Biomimetic device and foreign body reaction cooperate for efficient tumour cell capture in murine advanced ovarian cancer - Lorena Alonso-Alconada; Alexandre de la Fuente; María Santacana; Alba Ferreiros; Rafael Lopez-Lopez; Xavier Matias-Guiu; Miguel Abal (The Company of Biologists, 2020)
Metastasis is facilitated by the formation of pre-metastatic niches through the remodelling of the extracellular matrix (ECM) promoted by haematopoietic and stromal cells. The impact of these primed sites is pronounced for intraperitoneal metastases, where the cavity-exposed ECM supports the attachment of the disseminating tumour cells. Likewise, implantation of biomaterial scaffolds influences metastatic progression systemically through a foreign body reaction (FBR). In this study, we integrated the concept of creating an artificial niche to capture tumour cells actively disseminating in the peritoneal cavity with a therapeutic strategy modulating the interactions of metastatic cells with the ECM. The aim was to transform a disseminated disease into a focal disease. For this, we designed and developed a 'biomimetic' ECM composed of a nonresorbable three-dimensional scaffold with collagen coating and characterized the FBR to the implanted biomaterial. We also analysed the safety of the implanted devices and their ability to capture tumour cells in different murine preclinical models of advanced ovarian cancer. Implantation of the biomimetic devices resulted in an initial inflammatory reaction that transformed progressively into a fibrous connective tissue response. The adhesive capabilities of the scaffold were improved with the ancillary effect of the FBR and showed clinical utility in terms of the efficacy of capture of tumour cells, disease focalization and survival benefit. These results demonstrated the performance and safety of this 'biomimetic' ECM in preclinical models of advanced ovarian cancer. Translated into the clinical setting, this new therapeutic strategy represents the possibility for control of peritoneal carcinomatosis upon primary ovarian debulking surgery and to expand the percentage of patients who are candidates for second rescue surgeries at the time of relapse.